2015
DOI: 10.2105/ajph.2014.302222
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Smoking Cessation Between Education Groups: Findings From 2 US National Surveys Over 2 Decades

Abstract: Objectives We examined smoking cessation rate by education and determined how much of the difference can be attributed to the rate of quit attempts and how much to the success of these attempts. Methods We analyzed data from the National Health Interview Survey (NHIS, 1991–2010) and the Tobacco Use Supplement to the Current Population Survey (TUS-CPS, 1992–2011). Smokers (≥ 25 years) were divided into lower- and higher-education groups (≤ 12 years and > 12 years). Results A significant difference in cessat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 45 publications
2
39
1
2
Order By: Relevance
“…Higher education has also been shown to be beneficial in smoking-cessation programs. 35 Therefore, education should be analyzed as an important variable in the relationship between smoking and gingival inflammation. Our finding of a positive association of VPI with gingival inflammation fits with prior studies that associated plaque with gingival inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Higher education has also been shown to be beneficial in smoking-cessation programs. 35 Therefore, education should be analyzed as an important variable in the relationship between smoking and gingival inflammation. Our finding of a positive association of VPI with gingival inflammation fits with prior studies that associated plaque with gingival inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The studies generally found greater odds of cessation among higher educated smokers [ 4 , 15 ] whereas smoking was shown to be inversely related to labour market attachment and earnings [ 16 ]. Some suggested that the inequalities in quitting rates widened over time, arguably as a result of implemented tobacco control policies [ 5 , 17 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…One important pathway relating education to health and mortality is health behavior [1, 2]. As such, a growing literature focuses on elucidating disparities in health behavior by educational attainment, with many studies showing that individuals with higher education exhibit more positive behavior [3, 4, 5, 6]. This research, however, often treats behaviors individually, thereby obscuring broader patterns of behavior that emerge within individuals [1].…”
mentioning
confidence: 99%